2022
DOI: 10.3389/ti.2022.10332
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Management in Solid Organ Transplant Recipients: A Pre-COVID-19 Survey From the Working Group of the European Society for Organ Transplantation

Abstract: Infections are leading causes of morbidity/mortality following solid organ transplantation (SOT) and cytomegalovirus (CMV) is among the most frequent pathogens, causing a considerable threat to SOT recipients. A survey was conducted 19 July–31 October 2019 to capture clinical practices about CMV in SOT recipients (e.g., how practices aligned with guidelines, how adequately treatments met patients’ needs, and respondents’ expectations for future developments). Transplant professionals completed a ∼30-minute onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 37 publications
(59 reference statements)
1
29
0
Order By: Relevance
“…It is difficult to determine the reasons for these discrepancies. A large survey from the Working Group of the European Society for Organ Transplantation (adults) noted similar discrepancies in the management of CMV and suggested that may be related to budgetary or reimbursement policies in specific countries (8). However, our survey showed very similar results and a nonuniform approach despite France having the same reimbursement policy for all children and limited budgetary limitations, especially for medications recommended by international guidelines.…”
Section: Discussionsupporting
confidence: 54%
“…It is difficult to determine the reasons for these discrepancies. A large survey from the Working Group of the European Society for Organ Transplantation (adults) noted similar discrepancies in the management of CMV and suggested that may be related to budgetary or reimbursement policies in specific countries (8). However, our survey showed very similar results and a nonuniform approach despite France having the same reimbursement policy for all children and limited budgetary limitations, especially for medications recommended by international guidelines.…”
Section: Discussionsupporting
confidence: 54%
“…However, the effect of preemptive therapy on CMV indirect effects is uncertain, including on preventing opportunistic infections [ 7 ]. In a recent survey that assessed prevention strategies from 224 transplant centers, it was shown that universal prophylaxis is used in 90% of centers in D+/R− SOT patients [ 8 ]. Kidney and heart-transplant patients are mostly treated for 6 months and lung-transplant patients are given 12 months prophylaxis, while 50% of liver-transplant patients were treated for 3 months and 50% for 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney and heart-transplant patients are mostly treated for 6 months and lung-transplant patients are given 12 months prophylaxis, while 50% of liver-transplant patients were treated for 3 months and 50% for 6 months. Among CMV-seropositive patients, 50% of centers use a prophylaxis strategy while the others prefer a preemptive strategy [ 8 ]. In liver-transplant patients, preemptive therapy is preferred in seropositive patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations